Project Method in Adult Education: Self-Experience Analysis - Lasmane, Ija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The project methodhas swiftly gained ground in education and it has nowbecome integral to the education process offering new ways for modernizing the education environment.Implementing projects provides learning opportunities for all of the involved parties – students, teachers, school principals and parents. In this article the Author has analysed the characteristics of the project method and the differences between project-based adult learningand non-adult learning,and the impact ofglobalization on projects. Projects can be implemented not only in the scope of specific subjects or specific schools but also as cooperation projects among schools of different countries. Based on the Author’s experience in international school cooperation projects and by applying the biographicmethod, the Author has analysed professional growth in the context of international projects in different project phases – planning, implementation and evaluation.The object of research – to analyse personalexperience in participating in international projects by applying the method ofbiographic reflection andto establish, through self-experience analysis, the potential impact of projects on the upgrading of contemporary school’s pedagogical process.